2012
DOI: 10.1111/j.1574-6941.2012.01386.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Vibrio fischeri genes are involved in biofilm formation and host colonization

Abstract: Biofilms are increasingly recognized as the predominant form for survival in the environment for most bacteria. The successful colonization of Vibrio fischeri in its squid host Euprymna tasmanica, involves complex microbe-host interactions mediated by specific genes that are essential for biofilm formation and colonization. In the present investigation, structural and regulatory genes were selected to study their role in biofilm formation and host colonization. We have mutated several genes (pilT, pilU, flgF, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…Perhaps symbionts in E. tasmanica are selected for better host tissue attachment and elevated stress tolerance (more sticky and hardy), while those in E. scolopes are evolutionarily honed for chemotaxis (more nimble locomotion and elevated nutrient sensitivity). Biofilm formation is positively correlated in many host-associated vibrios with colonization potential, immunity avoidance, and eukaryotic cell attachment in hosts [5759]. Biofilms are known to increase bacterial survival against environmental stress [5861].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps symbionts in E. tasmanica are selected for better host tissue attachment and elevated stress tolerance (more sticky and hardy), while those in E. scolopes are evolutionarily honed for chemotaxis (more nimble locomotion and elevated nutrient sensitivity). Biofilm formation is positively correlated in many host-associated vibrios with colonization potential, immunity avoidance, and eukaryotic cell attachment in hosts [5759]. Biofilms are known to increase bacterial survival against environmental stress [5861].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, type-4 pili (T4P) are a class of surface structures often associated with pathogenic or beneficial microbial colonization of host tissue (Craig et al, 2004;Dulla et al, 2012), and 10 distinct T4P gene clusters have been identified in V. fischeri strain ES114 (Ruby et al, 2005). Some of these putative pilus proteins (that is, MshA, PilT and PilA2) have been linked previously to the colonization process Ariyakumar and Nishiguchi, 2009;Chavez-Dozal et al, 2012). As expected, these pili are encoded in the genomes of all the light organ-derived strains (Table 2).…”
Section: Mauve-gene Distributionmentioning
confidence: 99%
“…We also selected mutant Vibrio fischeri strains (from the ETJB1H isolate) that have been reported to be defective in biofilm formation (Ariyakumar and Nishiguchi 2009; Chavez-Dozal et al 2012). Mutant strains had interruptions in genes responsible for: (a) twitching motility and pilus assembly (Δ pilT , Δ pilU , Δ mshA ; Ariyakumar and Nishiguchi 2009; Chavez-Dozal et al 2012), (b) flagellum assembly and functionality (Δ flgF , Δ motY ; Chavez-Dozal et al 2012), (c) stress responses such as heat shock (Δ ibpA ) and magnesium-dependent induction (Δ mifB ; Chavez-Dozal et al 2012). …”
Section: Methodsmentioning
confidence: 99%
“…Aliquots of each Vibrio isolate (200 µL) were added to individual wells on a flat-bottom, polystyrene 96-well microtitre plate (Corning, Sigma Aldrich CLS3628, St. Louis, MO) and incubated for 24 h under conditions previously described (Chavez-Dozal et al 2012). After incubation, planktonic (those not forming biofilms) cells were removed by briskly shaking the plate and attached cells were washed three times with sterile media.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation